The Portuguese business cycle: chronology and duration dependence - Castro, Vítor (2011)
This paper tries to identify, for the first time, a chronology for the Portuguese business cycle and test for the presence of duration dependence in the respective phases of expansion and contraction. A duration dependent Markov-switching vector autoregressive model is employed in that task. This model is estimated over monthly and year-on-year (monthly) growth rates of a set of relevant economic indicators, namely, industrial production, a composite leading indicator and, additionally, civilian employment. The estimated specifications allow us to identify four main periods of contraction during the last three decades and the presence of positive duration dependence in contactions, but not in expansions.